Awareness among employers and employees on hazard in construction sites / Thahirah Abdul Rashid - Abdul Rashid, Thahirah (Faculty Architecture, Planninng and Surveying, 2015)
Statistic shown that the number of hazard in the Malaysia construction sites is one of the highest as compared to other sector. The parties involved in the construction industry strive continuously to reduce accidents and high mortality rates among workers at construction sites. The accidents in construction sites are still in an issue that is frequently reported in the media nowadays. The objective of this study is to investigate the awareness level among employers and employees towards hazards in constructions sites and to examine the possible causes of lack of awareness among employers and employees towards hazard in constructions sites. This study focuses only on the Klang Valley area which is involved the construction sites in Section 13, Shah Alam, Section 7, Shah Alam and Precint 15, Putrajaya. The studies were conducted through literature review and interview to get the result accurately and comprehensively. The three case studies were conducted on Class A contractors in Klang Valley area who are actively involved in the implementation of construction projects as respondents for feedback in relation to aspects of this research. The result of this research showed that the causes of the accident which occurred at a construction site identified as a result of poor attitude towards safety,some people in construction sites has poor in their self-control, failure to learn lessons from previous incidents, poor management practises, deficient enforcement of safety and etc. It is expected that the parties involved in safety and health at construction sites can apply the findings of this study to predict and thus make planning and regulation with more efficiently.